Amelioration of Lipid Metabolic Profiles by Trigonelline a Bioactive Compound of Trigonella Foenum-graecum in Alcohol Induced Albino Rats - Meesala Guru Sekhar , Kondeti Ramudu Shanmugam2 Kanchi Siva Prasad3 Ramakrishna Chilakala; Kondeti Ramudu Shanmugam Kanchi Siva Prasad3 Ramakrishna Chilakala4
: Alcoholism leads to heart diseases, lung diseases and liver disorders. Alcoholism impairs heart homeostasis and causes cardio vascular diseases. The current investigation was carried out to know the hypolipidemic effect of Trigonelline (TG) a bioactive compound of Trigonella foenum-graecum (TGf) in alcohol intoxicated rats. Materials and Methods: The rats were randomized into five groups and treatment was given as per the experimental protocol. The lipid metabolic profiles like Malondialdehyde (MDA), Total Cholesterol (TC), Triglycerides (TGs), High-Density Lipoprotein (HDL), Low-Density Lipoprotein (LDL), Very-Low-Density Lipoprotein (VLDL), and liver markers Alkaline Phosphatase (ALP), Alanine Aminotransferase (AAT), Aspartate Aminotransferase (AST) were estimated in the serum of all experimental groups. Results: All the lipid metabolic profiles and AAT, AST, ALP elevated in alcohol treated group, except HDL. This may be due to the alterations in lipid metabolism, which leads to hypercholesterolaemia and alcohol induced liver damage. Whereas with trigonelline treatment in alcoholic rats, these lipid metabolic profiles and liver markers were normalized and came back to normal levels. Further histopathological observations also proved that trigonelline protected heart tissue from alcohol toxicity in rats. Conclusion: Our findings suggest that trigonelline modulated the lipid metabolic profiles in alcohol intoxicated rats, hence trigonelline might be effective for preventing or treating alcohol related disorders and lipid related diseases.